PENYULUHAN TENTANG ‘READING STRATEGIES IN DIGITAL ERA DI MTS AS-SA’ADIYAH SAMARINDA - Bali Geroda, Godefridus; Oktaviani, Monica (Fakultas Keguruan dan Ilmu Pendidikan Universitas Widya Gama Mahakam Samarinda, 2023)
Reading is very important for English learners because reading can enlarge their knowledge, vocabulary, and information. From reading, English learners also can learn about foreign language people's habits and cultures. Students should know why before teaching reading, a lecture should inform students about their purpose first. Knowing the purpose first is important for them since by understanding the purpose of reading, the students can focus on what they want so that they can read effectively. The problem of the study is: